A bubble column evaporator with basic flat-plate condenser for brackish and seawater desalination. Issue 1 (2nd January 2016) - Schmack, Mario; Ho, Goen; Anda, Martin
Abstract : This paper describes the development and experimental evaluation of a novel bubble column-based humidification–dehumidification system, for small-scale desalination of saline groundwater or seawater in remote regions. A bubble evaporator prototype was built and matched with a simple flat-plate type condenser for concept assessment. Consistent bubble evaporation rates of between 80 and 88 ml per hour were demonstrated. Particular focus was on the performance of the simple condenser prototype, manufactured from rectangular polyvinylchlorid plastic pipe and copper sheet, a material with a high thermal conductivity that quickly allows for conduction of the heat energy. Under laboratory conditions, a long narrow condenser model of 1500 mm length and 100 mm width achieved condensate recovery rates of around 73%, without the need for external cooling. The condenser prototype was assessed under a range of different physical conditions, that is, external water cooling, partial insulation and aspects of air circulation, via implementing an internal honeycomb screen structure. Estimated by extrapolation, an up-scaled bubble desalination system with a 1 m 2 condenser may produce around 19 l of distilled water per day. Sodium chloride salt removal was found to be highly effective with condensate salt concentrations between 70 and 135 µS. Based on findings and with the intent to reduce material cost of the system, a shorter condenser length of 750 mm for the non-cooled (passive) condenser and of 500 mm for the water-cooled condenser was considered to be equally efficient as the experimentally evaluated prototype of 1500 mm length. GRAPHICAL ABSTRACT: